DESIGNED A PROTOCOL BASE AS THE DRIVING FORCE FOR THE FREIGHT LIFT IN BUILDING I OF PEMBANGUNAN PANCA BUDI UNIVERSITY - Hamdani, Hamdani; Winata, Rori Efriansa (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
The protocol base system is a communication from Arduino to other Arduino, this communication can be used by more than 10 Arduino, in this case one Arduino is used as a protocol base so that it only functions as a signal receiver and sender, while as a signal provider and receiver there are four other Arduino which have their respective programs in it and every command from each Arduino is connected to each other so that there is no miss communication. Here is how the base protocol system works. When the lift has been opened for access, Arduino 1 gives a signal to Arduino 5 that the lift has been opened for access, then Arduino 5 sends a signal to Arduino 3 to issue a notification that the lift can be accessed. When the lift reaches the destination floor Arduino 2 gives a signal to Arduino 5 that the lift has arrived at the destination floor, then Arduino 5 gives a signal to Arduino 3 to notify the user that the lift has arrived and also simultaneously gives a signal to Arduino 1 so that re-closing the lift again so that it is not used carelessly. When the lift load is overloaded Arduino 4 gives a signal to Arduino 5 that the lift is overloaded, Arduino 5 gives a signal to Arduino 3 to notify that the lift is overloaded and sends a signal to Arduino 2 to turn off the motor power supply so that the motor does not move.